Lenguaje y mundo social: la relevancia pragmática del lenguaje - Acevedo, Mariela Hemilse (Nómadas. Critical Journal of Social and Juridical Science, 2011)
The intention in these pages is to make a brief description of the bonding that Alfred Schutz and Ludwig Wittgenstein proposed between ordinary language and the social world, trying to account for those formulations that problematized the question the pragmatic nature of meaning.